Investigating the Impact of Pores on Rock Damage during Thermal Spalling Drilling - Liu, Weiji; Yang, Feilong; Zhu, Xiaohua (International Journal of Petroleum Technology, 2023)
Numerous microcracks and pores in geological rock formations cause early flaws. High temperatures increase these fractures and pores, thermally damaging reservoir rocks and changing the rock failure mechanism. However, research on pores’ high-temperature thermal spalling and fragmentation effects on heterogeneous rocks is sparse. This study built a finite element numerical model of heterogeneous granite rock thermal damage with pores based on rock thermal fracture theory and the Voronoi method and explored the mechanism under varied pore settings. The research’s findings indicate that the application of high temperatures to local heterogeneous porous rocks results in a higher proportion of tensile damage. The proportion of shear damage and tensile damage constantly varies due to the changing position and shape of the pores. The rock’s porosity has the effect of decreasing temperature in the direction of heat transfer while increasing the extent of temperature transfer along the pore parallel to the heating surface. The potential degree of damage increases as the density of pores increases, the distances between them decrease, and the pore lengths increase. The thermal damage resulting from heating in the vicinity of the pore is primarily localized in the area between the pore and the heated surface. This effect becomes more significant as the distance between them decreases. The findings of this study can serve as a theoretical framework for understanding the impact of rock pores on rock thermal fracturing and fragmentation in the thermal spalling-assisted development of deep oil and gas resources.